Effects of Short‐Term Climate Variations on Young Water Fraction in a Small Pre‐Alpine Catchment - C. Xia; G. Zuecco; C. Marchina; D. Penna; M. Borga (Water Resources Research)
Abstract Continuous and extended observations of hydrometeorological parameters, alongside the analysis of the isotopic composition across diverse waters within catchments, can significantly enhance our understanding of the potential ramifications of climate change on the hydrological response. In this study, a comprehensive analysis of hydrometeorological and isotopic data was conducted over 10 hydrological years (October 2012–September 2022) within a small, forested catchment in the Italian pre‐Alps, aiming to investigate the impacts of short‐term climatic changes on the isotopic composition of waters and the young water fraction (Fyw). The results showed that the catchment experienced climate conditions with rapid warming and drying trends. Significant isotopic enrichments were observed in all sampled water sources, driven primarily by air temperature. Fyw was estimated to be 0.64 ± 0.06, 0.45 ± 0.07, and 0.16 ± 0.03 for stream water, soil water, and shallow groundwater based on the whole‐period sinusoidal fittings, respectively. Comparative analyses comprising different approaches for the estimation of Fyw showed that time‐windows scenarios and detrending corrections yielded smaller Fyw than approaches based on the whole‐period fitting and discharge‐sensitivity modeling. Such differences can be attributed to an uneven temporal distribution of stream water isotopic data, the difficulties in capturing high flows in a humid catchment characterized by a fast runoff response during rainfall‐runoff events, and the presence of isotopic trends. Our findings underscore the imperative of integrating interannual isotopic trends and adopting appropriate sampling strategy and methodological approaches to ensure a robust Fyw estimation.